1994
DOI: 10.1021/j100056a002
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Gating of Intramolecular Electron Transfer

Abstract: The rates for ionic photodissociation of malachite green leucocyanide to form cyanide ion and a malachite green carbonium ion were measured as a function of solvent and temperature. The observed rates in mixtures of polar and nonpolar solvents all had an activation energy of about 1 kcal/mol for a wide range of dielectric constants. This dissociative intramolecular electron transfer (DIET) is unusual because it is the first example where solvent configurational entropy changes are required to enable a large am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…49 Fluorescence and intersystem crossing (isc) account for the S 1 decay of dialkylanilines, and they are good models for the S 1 of TAM-CNs in nonpolar solvents. 25,30,33 The fluorescence emission spectrum of 1 is characteristic of the S 1 (ππ*) state of DMA/DMT. The fluorescence quantum yield (φ fl ) decreases with increasing solvent polarity (Table 1), while the efficiency of coloration increases.…”
Section: Cvcn Spectral Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…49 Fluorescence and intersystem crossing (isc) account for the S 1 decay of dialkylanilines, and they are good models for the S 1 of TAM-CNs in nonpolar solvents. 25,30,33 The fluorescence emission spectrum of 1 is characteristic of the S 1 (ππ*) state of DMA/DMT. The fluorescence quantum yield (φ fl ) decreases with increasing solvent polarity (Table 1), while the efficiency of coloration increases.…”
Section: Cvcn Spectral Characteristicsmentioning
confidence: 99%
“…Note the ionization reaction does not occur from T 1 . [27][28][29]31,33 Steady-State Photolysis. (a) UV-vis.…”
Section: Cvcn Spectral Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The photodissociation reaction in TAMCNs is critically dependent on solvent polarity (no dye formation in solvents with e below 4.5) 27 and proceeds from thermally equilibrated S 1 excited state 28 in competition with fluorescence and intersystem crossing. The active role of the solvent has been elucidated in a study on malachite green leuconitrile (MGCN) by Spears et al 29,30 who showed that the dissociative intramolecular electron transfer is assisted by solvent configurational entropy changes that are required to enable large amplitude molecular distortion leading to a non-adiabatic ET and ionic dissociation. A comparative study of DMA and MGCN reported by Brown and Cosa 31 showed similar behaviour of these compounds in cyclohexane and significant shortening of MGCN fluorescence lifetime in more polar solvents, indicating that the dissociative intramolecular ET process from the S 1 state in MGCN represents merely a relatively slow (sub-ns) quenching process of the primarily excited dimethylaniline chromophore.…”
Section: Introductionmentioning
confidence: 99%
“…The details of the reaction pathways for photoinduced homolysis and heterolysis, both occurring in less than 20 ps, have yet to be elucidated and thus we can only speculate on the processes leading to dissociation. Based upon the Miller and Spears model for solvent gating of intramolecular electron transfer, it is a fluctuation in the solvent structure that governs the decay of S 1 . Immediately following excitation, the solvent structure surrounding the first excited singlet state will be that corresponding to the equilibrium solvation structure for the reactant.…”
Section: Discussionmentioning
confidence: 99%